Bhasha bhushanathinte upadanangal - Unithiri, N V P. (Kerala Bhasha Institute, 2000)
Articles on source materials of Bhāṣābhūṣaṇaṃ, a work on Malayalam grammar and poetics by A. R. Rajaraja Varma, 1863-1918.